The Effectiveness of the STEM-based Differentiation Learning Model on Merdeka Curriculum Learning Outcomes - Yohanes Bowo Widodo; Miftachul Amri; Via Yustitia; Ni Desak Made Santi Dwyarthi; Adrie Oktavio; Andika Dirsa (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to determine the effectiveness of the STEM-based differentiation learning model on the results of independent curriculum learning. This type of research is quantitative research with a meta-analysis approach. This research data comes from 10 national journals published from 2021-2024. Search research data through the mendeley, google scholar, Wiley and Researchgate databases. The data collection technique is purposive sampling. The criteria for the data included in the meta-analysis are research published in the last 3 years 2021-2024; Research must be related to STEM-based differentiation learning on student learning outcomes in the independent curriculum, research must be open access, research comes from indexed journals Science Technology Index (SINTA) and Scopus and research reports complete data to calculate effect size values. Data analysis is quantitative data analysis by calculating the effect size value of each data with the help of the JAMOVI application. The results of the study concluded that STEM-based differentiation learning had a positive effect on the independent curriculum with an average effect size value of 1.06. These findings provide important information for teachers implementing STEM-based differentiated learning in schools.